HEROIC IDEAS IN BEOWULF AND LE MORTE D’ARTHUR: A COMPARATIVE STUDY OF MEDIEVAL HEROISM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The figure of the Indo-European Hero is deeply multifaceted, embodying both the highest virtues and the most destructive impulses of human nature. While heroes often reflect the most admirable ideals of their societies, they also carry within them a capacity for violence that can threaten even those they are meant to protect. In The Medieval Hero, Dr. Connell Monette explores a broad spectrum of heroic narratives from Celtic, Persian, and Anglo-Saxon traditions, uncovering the underlying truths about heroism—its origins, defining traits, sources of power, and the principles of the Heroic Code. Demonstrating remarkable expertise in historical languages, Monette presents readers with original excerpts alongside English translations from Classical Persian, Old Irish, Old English, and Classical Greek. This work provides valuable insight into the heroic figure in ancient and medieval epics and offers readers the tools to recognize key themes in contemporary reinterpretations of the heroic genre. A comparative analysis of Beowulf and Le Morte d’Arthur reveals a clear evolution in the concept of heroism—from the pagan model focused on individual strength and battlefield glory to the medieval ideal shaped by chivalric values and communal responsibility. Whereas Beowulf highlights extraordinary physical power and personal bravery as the essence of a hero,